2018
DOI: 10.1002/ijgo.12638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prophylactic uterine artery embolization on second‐trimester induced abortions in patients with placenta previa

Abstract: ChiCTR-OPC-14005334.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Does prenatal bleeding reoccur after UAE? Wang et al [36] observed that patients with CSP who underwent curettage within 24 hours after UAE had a 5.0% risk of intraoperative bleeding. However, this risk increased to 19.4% for those with a treatment interval longer than 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Does prenatal bleeding reoccur after UAE? Wang et al [36] observed that patients with CSP who underwent curettage within 24 hours after UAE had a 5.0% risk of intraoperative bleeding. However, this risk increased to 19.4% for those with a treatment interval longer than 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, total or subtotal hysterectomy [5,6] is needed to stop those life-threatening bleeding. Mifepristone combined with ethacridine lactate/misoprostol is common method used in the second-trimester pregnancy termination in China especially for those CPP patients [7] , and those methods of drugs are effective and safe [8,9] . How to deal with the prenatal bleeding during induction for CPP patients with unfavorable cervix in the second trimester is the focus of current clinical work.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, it had been reported that bilateral uterine arteries embolization could significantly reduce the risk of cesarean section, hysterectomy, and transfusion for patients with placenta previa induction of labor, when the fetus is unlikely to survive. [12][13][14] However, few data are known about whether prophylactic uterine artery embolization (PUAE) during cesarean delivery could reduce the risk of hemorrhage, transfusion, hysterectomy, and postoperative hospitalization time, in termination of pregnancy of patients with single complete placenta previa. So we aimed to evaluate the effectiveness and safety of PUAE during cesarean delivery, for controlling blood loss in patients with complete placenta previa.…”
Section: Introductionmentioning
confidence: 99%